1988
DOI: 10.1002/lsm.1900080305
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the rat lung from the harmful effects of laser smoke

Abstract: Fourteen Sprague-Dawley rats were exposed to CO2 laser exhaust that had first passed through smoke-evacuator filters. Six rats breathed laser vapors that were filtered through commercially available, standard production model smoke-evacuator systems. These animals demonstrated pulmonary lesions identical to but qualitatively less severe than those observed in animals breathing unfiltered vapor. Six additional rats were protected by the interposition of a cartridge filter plus an ultra-low penetration air filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 7 publications
0
44
0
Order By: Relevance
“…It has been clearly shown that laboratory rats develop pulmonary congestion and lung abnormalities when exposed to a relatively large quantity of surgical smoke [39]. Specifically, it has been shown that surgical smoke can induce acute and chronic inflammatory changes, including alveolar congestion, interstitial pneumonia, bronchiolitis, and emphysematous changes in the respiratory tract [40,41].…”
Section: Respiratory Irritationmentioning
confidence: 99%
“…It has been clearly shown that laboratory rats develop pulmonary congestion and lung abnormalities when exposed to a relatively large quantity of surgical smoke [39]. Specifically, it has been shown that surgical smoke can induce acute and chronic inflammatory changes, including alveolar congestion, interstitial pneumonia, bronchiolitis, and emphysematous changes in the respiratory tract [40,41].…”
Section: Respiratory Irritationmentioning
confidence: 99%
“…Other laboratory studies have demonstrated that smoke from both electrocautery and laser surgery is mutagenic to certain strains of Salmonella typhimurium (16,17). Animal studies have shown that repeated exposure to high levels of surgical smoke can induce inflammatory pulmonary changes, including emphysema and bronchiolitis (18)(19)(20)(21). Despite these laboratory and animal data, there are no population-based studies available to suggest whether or not repeated exposure to surgical smoke can induce carcinogenesis or chronic inflammation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory and animal studies indicate that surgical smoke has mutagenic potential and can induce inflammatory pulmonary changes in animals after repeated exposure (16)(17)(18)(19)(20)(21). On the basis of an in vitro assay, Tomita et al (16) estimated that the smoke produced during laser irradiation or electrocauterization of 1 gram of tissue is equivalent to three to six cigarettes in mutagenic potential.…”
mentioning
confidence: 99%
“…28 Studies have demonstrated that the particulate matter generated can cause pathological damage when deposited in mammalian lungs. 29,30 Currently, there are no mandates for control of surgical smoke. Specific recommendations published by the Association of PeriOperative Registered Nurses include using a combination of general room and local exhaust Volume 130, Number 5 • Operating Room Safety II ventilation.…”
Section: Surgical Smoke and Laser Plumementioning
confidence: 99%